(untitled) (Journal of Applied Learning and Teaching, 2022)
In March 2020, one Australian higher education provider, like many others, found itself pivoting into fully online teaching as the nation managed the COVID 19 pandemic and campuses closed. Bespoke professional learning workshops were offered to all staff, many of whom demonstrated the professional willingness to change their practices in order to offer students the highest quality learning experience that was possible in the demanding and unexpected conditions inherent in the pandemic. There were many challenges revealed through ongoing discussions amongst staff as a community of learners. Throughout the discussions, the concept of presence (Garrison, 2007, 2017) was recurring - teacher and student presence in the newly mandated online teaching context. The centrality of kindness was identified as a second concept that mediated academic discussions and emotions. Both concepts form the focus of this paper. The positioning of kindness within Garrison’s framework of inquiry (2017) will be proposed as a proposition that is worthy of further research particularly if higher education in Australia continues to be uncertain and fraught with change.